Construction and Validation of An Audiovisual Program on Body Education - Lessa, Risia Carine Maciel Meira Schwartz; Bacha, Elizabeth; Wanderley, Flávia Accioly Canuto (Advances in Social Sciences Research Journal, 2024)
To build and validate an audiovisual program as a resource to encourage body education. Study with a qualitative and quantitative methodological approach. The content was developed with a view to encouraging people who work predominantly seated to seek new well-being strategies based on (self-)knowledge of the body. For the development of the program, the contents were divided into scripts for 11 videos. All materials were built based on the CTM3 Method, a method for structuring educational products. Validation was carried out with the contribution of ten reviewers, five specialists and five laypersons. They evaluated the videos through a form composed of six questions. The criteria used for validation were a) Agreement Index (simple majority) and Content Validity Index (CVI ≥ 0.8). The body education program was validated with AI equal to or greater than 80% and CVI equal to or greater than 0.8. The content of the audiovisual program was considered valid for stimulating a culture of body education.